The phenomenology of self-critical thinking in people with depression, eating disorders and in healthy individuals - Thew, G; Gregory, J; Roberts, K; Rimes, K (Wiley, 2017)
Objectives: To explore the phenomenology of self-criticism, and the relationship with constructs such as rumination and perfectionism. Design: The study followed a three group (Depression, n=26; Eating Disorder, n=26; Nonclinical, n=26) mixed methods design. Method: Participants completed a set of questionnaires and were interviewed about the occurrence, impact, and content of self-critical thinking, along with their beliefs about selfcriticism. Results: Both clinical groups reported more frequent, persistent, and less controllable selfcriticism compared to controls, present on average 50-60% of the time. They reported a negative impact on mood, and a moderately severe impact on daily activities. They indicated greater desire to change self-criticism while judging it more difficult to reduce. Habitual selfcriticism was highly correlated with lower self-esteem, lower self-compassion, greater rumination and greater negative perfectionism. Compared to those with depression, the eating disorder group reported harsher self-criticism, felt it was more part of their personality, and was more beneficial. Conclusions: The findings highlight the importance of exploring people’s beliefs about their self-criticism, and imply that treatment for self-criticism may be more challenging with people with eating disorders than people with depression.